La Famille 13 dans l'évangile de Marc - Lafleur, Didier. (New Testament Tools, Studies and Documents, 2013)
As a first order witness of the Greek New Testament, Family 13 has a long history in the field of textual criticism. Nearly seventy years after Kirsopp and Silva Lake's publication, La Famille 13 dans l'évangile de Marc offers an enlarged, wholly up-to-date and thoroughly revised study of the text of the Gospel of Mark for the witnesses considered as family members by Didier Lafleur. His extensive survey includes the history of the discovery of the manuscripts, their codicological description and new research on the text. The most part of the book is devoted to the edition of minuscule 788 (Athens, Nat. Lib. 74), considered by the author as the nearest member to the archetype of the group ( f ¹³ ). Based on quite new collations for the all extant manuscripts, the edition provides a positive apparatus. Considérée comme témoin de premier ordre du Nouveau Testament grec, la Famille 13 s'enracine profondément dans l'histoire de la critique. Soixante-dix ans après la publication de Kirsopp et Silva Lake, La Famille 13 dans l'évangile de Marc offre un panorama exhaustif sur le texte de cet évangile pour les témoins considérés par Didier Lafleur comme membres de ce groupe ( f ¹³ ). Son étude englobe la mise en lumière des manuscrits, leur description codicologique et de nouvelles recherches philologiques. L'auteur édite le texte du minuscule 788 (Athènes, Bibl. nat. 74), qu'il considère comme le témoin le plus proche de l'archétype de la famille. Collationés à nouveaux frais pour le texte de Marc, tous les manuscrits de la Famille 13 apparaissent ici pour la première fois dans une édition critique.